The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1016/j.bbmt.2018.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus Infection Incidence and Risk Factors Across Diverse Hematopoietic Cell Transplantation Platforms Using a Standardized Monitoring and Treatment Approach: A Comprehensive Evaluation from a Single Institution

Abstract: Human cytomegalovirus (CMV) infection and disease remains a significant cause of morbidity and mortality for hematopoietic cell transplantation (HCT) recipients. Disruption of or weak reconstitution of virus-specific cellular immune function, such as with certain HCT approaches, poses significant risk for CMV-related complications. The incidence of and risk factors for CMV infection and the nature of CMV disease were evaluated retrospectively among 356 consecutive HCT recipients transplanted at the National In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 27 publications
(27 reference statements)
2
28
1
Order By: Relevance
“…No patients had clinically significant EBV-associated complications, consistent with outcomes previously published with PTCy-based approaches [51]. CMV reactivation was controlled with pre-emptive therapy alone in all but 1 patient, which could in part be associated with the use of sirolimus [16,52]. Notably, post-BMT primary CMV infection was not uncommon; all cases occurred after weekly CMV monitoring had stopped, and 1 case progressed to CMV disease.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…No patients had clinically significant EBV-associated complications, consistent with outcomes previously published with PTCy-based approaches [51]. CMV reactivation was controlled with pre-emptive therapy alone in all but 1 patient, which could in part be associated with the use of sirolimus [16,52]. Notably, post-BMT primary CMV infection was not uncommon; all cases occurred after weekly CMV monitoring had stopped, and 1 case progressed to CMV disease.…”
Section: Discussionsupporting
confidence: 81%
“…Epstein-Barr virus (EBV), cytomegalovirus (CMV), human herpesvirus 6, adenovirus, and BK virus were evaluated weekly in blood and, for BK virus, also urine by quantitative PCR. CMV monitoring and preemptive treatment were performed as previously published [16].…”
Section: Methodsmentioning
confidence: 99%
“…Cytomegalovirus (CMV) viremia occurs in 40% to D 1 2 7 X X90% of CMV-D 1 2 8 X Xseropositive recipients (R + ) [1À3] and is associated with increased overall mortality after hematopoietic cell transplantation (HCT) [4]. Risk factors for CMV reactivation after HCT are well established and include T D 1 2 9 X Xcell depletion, allograft from D 1 3 0 X XHLA-mismatched or CMV-seronegative donor (D ¡ ), and graft-D 1 3 1 X Xversus-D 1 3 2 X Xhost disease (GVHD) [1,4]. Preemptive therapy (PET) has reduced the rates of CMV end-organ disease to less than 5% [5], the trade-off being increased use of CMV antivirals with their associated toxicities and potentially prolonged hospital length of stay (LOS).…”
Section: Introductionmentioning
confidence: 99%
“…A summary of selected studies reporting CMV incidence can be found in Table 2. When compared to other graft sources, UCB transplants have been reported to have higher cumulative incidences of CMV infection and CMV disease 6, 26, 29 . The risk of CMV is also much higher in CMV seropositive recipients.…”
Section: Cytomegalovirus In Alternative Donor Transplantsmentioning
confidence: 99%